Evaluating The Effects Of Zoom Video Conferencing On Student Education: Applying The Technology Acceptance Framework - Salendab, Fahad A.; Jr, Avelino G. Ignacio; Vidal, Carmelo John; PhD, SANNY S. MAGLANTE; Jimenez, Vida D.; Soriano, Dr. Sonny; PhD, Leonilo B. Capulso (Migration Letters, 2024)
This research examines the Zoom video conferencing platform and using the Technology Acceptance Model (TAM) to elucidate the effects of adopting new technology on educational results. The study used structural equation modeling to examine the associations between the components of the Technology Acceptance Model (TAM) and the Zoom lessons conducted during the COVID-19 epidemic. A cross-sectional research design was employed to interview 323 Asian university students who were in their 10th week of an English as a foreign language (EFL) conversational English class. The interview included measures of perceived ease of use (PeU), perceived usefulness (P.US.), behavioral intentions, and P.uS. attitude scales (Scheper et al., 2019). Out of the 10 hypotheses tested, 7 were supported by path coefficients that varied in attitude. One significant impact of PeU was its effect on both intended and actual use of Zoom. Furthermore, the students’ self-assessments of their learning remained untouched by the perceived usefulness of Zoom. However, it did have a significant impact on their plans to use Zoom in the future. Although P.US. was helpful in predicting students’ future behavior, it did not impact their evaluations of their current accomplishment in their video conference class. Video conferencing technology had a significant influence on students’ perceptions of their own development, P.uS. attitudes, and the applicability of the information they acquired via collaborative learning. P.US. mediated two significant occurrences, thereby resolving the problem. Upon careful examination of the results, it is evident that students must get thorough guidance on the use of video conference software prior to integrating it into their video conference classes.